Diagnosis, Prophylaxis, and Treatment of Headaches in the Athlete - Swain, R. A.; Kaplan, B. (Southern Medical Journal, 1997)
Background. Headaches are a common entity in the ambulatory population. Physicians involved in sports medicine must be able to accurately diagnose headaches in athletes and whether they are exacerbated by exertion. Many medications have proven or theoretical negative effects on athletic performance. Thus, we should consider all aspects of medical management and determine which therapy is least intrusive to the athleteís performance. We planned this review because of the small number of papers available on the effects of various medications on athletic performance. Methods. We used MEDLINE to search from 1992 to current citations, using the medical subject headings of headache, prophylaxis, treatment, review, athletes, and exercise, alone or in combination. Results. Fifty-two articles were identified and deemed appropriate for inclusion in this review. Conclusions. Acute therapy for tension headaches in the athletic population is best done with nonsteroidal anti-inflammatory drugs. Prophylaxis of chronic, recurrent tension headaches is best accomplished by night-time tricyclic antidepressants (especially nortriptyline) or selective serotonin reuptake inhibitors. Acute therapy for athletes with migraines is best managed with sumatriptan or DHE 45 and prophylaxis can be accomplished with verapamil, antidepressants, or valproate. Exertional, cluster, and structural/infectious headaches are also discussed briefly.